IMPLEMENTASI METODE TUSUK SATE UNTUK MENINGKATKAN MOTIVASI DAN KETERAMPILAN BERHITUNG PADA MATERI PEMBAGIAN BILANGAN - Dwi Putri, Sulistiani; Ayu Yudianti, I Gusti; Huda, Samsul; Hasanah, Tita (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
This service activity aims to implement the skewer method in calculating number division for students. Participants in this service activity were class V students at MI Miftahul Hidayah. The service method used is Participatory Action Research. The results of this service show that with the skewer method students can more easily understand and complete division calculations on numbers. Students are more motivated in learning to count and improve students' numeracy skills. Through this activity, it was revealed that the skewer method was able to motivate and improve counting skills in number division material